Power Relations, Investment Prospects, and Social Responsibility in Corporate Tax Avoidance Practices of Energy Companies in Indonesia 2020-2024: Relasi Kekuasaan, Prospek Investasi, dan Tanggung Jawab Sosial dalam Praktik Penghindaran Pajak Perusahaan Energi di Indonesia 2020-2024 - Famela Gadis; Tri Joko Prasetyo; Retno Yuni Nur Susilowati (Academia Open, 2026)
General Background: Corporate tax avoidance remains a critical issue when tax revenue contributions are considered suboptimal, particularly in sectors characterized by volatility. Specific Background: In Indonesia’s energy sector, recurring concerns about tax planning practices have motivated renewed empirical attention to governance- and disclosure-related determinants. Knowledge Gap: Prior studies report inconsistent conclusions regarding the relationship between politically affiliated corporate structures, investment opportunity conditions, and corporate social responsibility disclosure in relation to tax avoidance. Aims: This study examines these relationships in energy sector companies listed on the Indonesia Stock Exchange over 2020–2024 using panel data from annual and sustainability reports and estimation with a Random Effect Model in EViews. Results: Based on 41 firms (164 firm-year observations), political connections are statistically non-significant, while investment opportunities (market-to-book value) and corporate social responsibility disclosure (GRI-based index) are each negatively and significantly associated with tax avoidance as measured by the gap between the corporate income tax rate and GAAP effective tax rate; the adjusted R-squared is 0.0481. Novelty: The study consolidates political affiliation, investment opportunity conditions, and GRI-based CSR disclosure within a single energy-sector panel for Indonesia during 2020–2024. Implications: The findings suggest that stronger market-oriented growth prospects and higher CSR disclosure coincide with lower levels of tax avoidance indicators in listed energy firms, while political affiliation presence alone does not provide a statistically reliable explanation within the tested model. Highlights: Board-level political affiliation shows non-significance in the panel regression results. Higher market-to-book value corresponds to a smaller statutory-rate versus GAAP-ETR gap. Greater GRI-based sustainability disclosure corresponds to a smaller statutory-rate versus GAAP-ETR gap Keywords: Revenue, Energy, Avoidance